Quantitative structure-activity relationships of perfluorinated hetero-hydrocarbons as potential respiratory media. Application to oxygen solubility, partition coefficient, viscosity, vapor pressure, and density - Gabriel, J L; Miller, Jr, T F; Wolfson, M R; Shaffer, T H (ASAIO journal (1992), 1996)
It has been extensively reported that liquid-assisted ventilation, using inert perfluorocarbon liquids (PFCs), can reduce interfacial surface tension and allow for improved ventilation at decreased alveolar pressures. PFCs are bioinert, minimally absorbed, and have no deleterious histologic, cellular, or biochemical effects when used as respiratory media. Although several types of PFCs have been characterized, a select few are considered to be compatible with life. Compatibility is often related to the physicochemical profile inherent to the PFC liquids. It is essential that certain physical properties such as respiratory gas solubility, vapor pressure, density, viscosity, and tissue permeability be within a narrow, acceptable range for a PFC to be considered as a possible candidate for respiratory media. The current study sought to characterize the physicochemical profile of commercially available PFCs. This was accomplished by creating a method for accurate, rapid prediction of a host of unknown physical characteristics of PFCs. The physicochemical properties of 16 perfluorinated hetero-hydrocarbons were catalogued from the literature. The input data were categorized into three major groups: empiric properties, geometric indices, and quantum mechanical descriptors, to generate a database. Algorithms were then developed, one for each dependent variable (FUNCTION), including oxygen solubility, partition coefficient (logP), vapor pressure, viscosity, and density, that related the values of these physical properties of potential breathable PFC liquids to the parameters listed in the database. The general form of the algorithm can be written as follows: FUNCTION = sigma (CiPi/magnitude of Pi) + constant; where the FUNCTIONS are oxygen solubility, logP, vapor pressure, viscosity, and density. Ci is a coefficient that weights the relative contribution of each parameter. Each independent parameter, Pi, was normalized by the average value of the parameter used in the analysis, magnitude of Pi. Residual analysis demonstrated validity with all five equations. This method is expected to assist in the prediction of physical properties of PFC liquids with acceptable accuracy, such that PFC production and selection from currently available liquids can be optimized for each liquid ventilation application.